2011
DOI: 10.1177/0022002711400862
|View full text |Cite
|
Sign up to set email alerts
|

Peace and War With Endogenous State Capacity

Abstract: We explore how peace or war can occur in the presence of commitment problems. These problems can be reduced by institutions of good governance or, alternatively, state capacity which (a) can be considered a collective good and (b) can be improved through investments. We show how the likelihood of a peace agreement depends on the level of state capacity and on investments in state capacity made by adversaries. In accordance with existing evidence but contrary to various theories of conflict, we find that income… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 34 publications
(36 reference statements)
1
26
0
Order By: Relevance
“…This question is far from settled, however, as other studies have found that UN intervention has had no statistically significant impact on democratization (Fortna and Huang, 2012) and that intervention can prolong war (Cronin, 2010). Outsiders, either unwittingly, or because of conflicting objectives, also may undermine state capacity (McBride et al, 2011).…”
Section: Review Of the Literaturementioning
confidence: 97%
See 1 more Smart Citation
“…This question is far from settled, however, as other studies have found that UN intervention has had no statistically significant impact on democratization (Fortna and Huang, 2012) and that intervention can prolong war (Cronin, 2010). Outsiders, either unwittingly, or because of conflicting objectives, also may undermine state capacity (McBride et al, 2011).…”
Section: Review Of the Literaturementioning
confidence: 97%
“…There is a sizeable literature on the role of UN intervention and it produces mixed conclusions on its effectiveness at either building state capacity or creating lasting peace. McBride et al (2011) suggest that outsiders can play a critical role in encouraging power sharing through investments in state capacity. Put another way, external intervention may influence democratization by allowing for the formation of credible commitments (Walter, 2001;Fortna, 2004).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…But, why this might be the case is not theoretically clear. One possibility is that higher levels of income are associated with better institutions and state capacity (McBride et al, 2011). Another, possibly complementary reason particularly in the case that the conflict is resource-driven has to do with the labor intensity of the production of resources over which conflict takes place.…”
Section: Correlates Of Peace and Conflictmentioning
confidence: 99%
“…McBride et al . () study a model of conflict between two parties in which two adversaries first undertake their one‐time investments in state capacity capital, and then, after observing their levels of state capacity, the two adversaries decide how much to arm and whether to engage in conflict.…”
Section: Introductionmentioning
confidence: 99%